2020
DOI: 10.1021/jacs.0c08631
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Tunable and Site-Selective Olefin Transposition

Abstract: The catalytic isomerization of C−C double bonds is an indispensable chemical transformation used to deliver higher-value analogues and has important utility in the chemical industry. Notwithstanding the advances reported in this field, there is compelling demand for a general catalytic solution that enables precise control of the CC bond migration position, in both cyclic and acyclic systems, to furnish disubstituted and trisubstituted alkenes. Here, we show that catalytic amounts of an appropriate earthabund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…More recently, Koh and co‐workers have reported an elegant regiodivergent isomerization process that uses B 2 pin 2 or PhMe 2 SiBpin in conjunction with an iron catalyst and LiO t Bu. Mechanistic studies revealed that the reaction is likely to proceed via an iron‐hydride with subsequent olefin insertion and β‐hydride elimination [12] . Pertinent to this study, Smith has employed an Fe I species, exploiting the propensity for spin crossover, to achieve iron catalyzed double bond isomerization via a two‐electron catalytic cycle [13] …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, Koh and co‐workers have reported an elegant regiodivergent isomerization process that uses B 2 pin 2 or PhMe 2 SiBpin in conjunction with an iron catalyst and LiO t Bu. Mechanistic studies revealed that the reaction is likely to proceed via an iron‐hydride with subsequent olefin insertion and β‐hydride elimination [12] . Pertinent to this study, Smith has employed an Fe I species, exploiting the propensity for spin crossover, to achieve iron catalyzed double bond isomerization via a two‐electron catalytic cycle [13] …”
Section: Introductionmentioning
confidence: 95%
“…Mechanistic studies revealed that the reactioni sl ikely to proceed via an iron-hydride with subsequent olefin insertion and b-hydride elimination. [12] Pertinent to this study, Smith has employed an Fe I species, exploiting the propensity for spin crossover, to achieve iron catalyzed double bond isomerization via at wo-electron catalytic cycle. [13] From the synthetic studies we have already disclosed in hydrofunctionalizationc hemistry, [14] we postulated that access to at wo-electron isomerization catalytic cyclew ould be possible by limiting the quantityo fh ydrides ource employed in order to access Fe I ,m eanwhilep reventing competitive Fe II hydroboration.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is growing interest in the field of remote functionalization as it allows for the formal activation of unreactive CH bonds distant from an initial reactive site without employing strongly coordinating directing groups 9 . In light of this, combining the present hydroamination protocol with our previously reported Fe-catalysed olefin migration methodology 10 , in a sequential fashion enables net remote hydroamination of terminal alkenes to afford the desired arylamines. This is noteworthy since the β position (vicinal to aryl groups) is typically less activated.…”
Section: Scheme 1 Representative Strategies Employed For Alkene Hydroaminationmentioning
confidence: 86%
“…The pincer-crown ether catalyst 2-18c6b is one of a select few catalysts capable of facilitating a single positional isomerization with exceptional stereoselectivity for the E-isomer. 5,[52][53][54][55][56] It is unique in selectively accessing either of two internal isomers in response to an external stimulus.…”
Section: Discussionmentioning
confidence: 99%